Potensi dan keterbatasan backhand pendek di bulu tangkis: Analisis kinematika - Irawan, Fajar Awang; Ma’dum, Mirza Arif; Indardi, Nanang; Trans, Minh Nghia Le; Fatmasari, Annisa Putri (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
Moreover backhand short serve is an important element of the main character in badminton, where not many people can maximize the potential and limits of each athlete, such as power, speed, accuracy, and motion efficiency. This study aims to determine the potential and weaknesses of short backhand serve in badminton through a kinematic analysis approach, with a sample of children aged 12-16 years PB Pendowo Semarang City. The method used quantitative with a descriptive analysis approach, and the analysis is assisted by using the Kinovea 0.9.4 series software. The sampling technique used is purposive sampling with two criteria; age (12-16 years old) and participation in a Semarang city-level tournament. The results showed that the PB Pendowo Semarang City athletes in the implementation phase are in the "Appropriate" category, with a percentage of 66.6%. The instruments used in this data collection are observation and documentation. Several factors that influence the level of conformity are muscle mass, arm length and height, and training intensity. This research can still be developed in future research by discussing more specific things, such as focusing on active wrists and, more specifically, explain about flick movement in the wrist motion. Additional supporting literacy in the backhand short serve analysis could help the athletes and coaches to reach effective movement to get points using the backhand short of serving as the first attack.